Formulation and Evaluation of Gambier (Uncaria gambir)-Chitosan Microparticle Intranasal Delivery for Alzheimer’s Diseases - Fithri, Najma Annuria; Mardiyanto; Fitrya; Rahmah, Asfaraeni; Annisa, Novilia Megi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Alzheimer’s Disease (AD), the most common form of dementia continues to be the deadliest neuro degenerative disease in recent years. Despite significant efforts to mitigate the progression of the disease, there is no known cure and development towards a more effective treatment is still lacking. AD is marked by exceptionally low amount of acetylcholine in the brain, formation of tau protein, and amyloid beta plaque. Current drugs of choice for treating AD, namely donepezil and memantine, are acetylcholinesterase (AChE) inhibitors which focused on delaying the onset of cognitive decline by maintaining acetylcholine concentration. Gambier water extract (GWE) contains high level of polyphenols which act as an antioxidant, exhibit strong correlation with AChE inhibitor. The aim of this research is to formulate and encapsulate GWE inside a microparticle system composed of chitosan and different crosslinkers, STPP (IMGS) and CaCl2 (IMGC), which were then characterized as AChE inhibitor using Ellman’s method. Variations of the formula were designed following Box-Behnken experimental design with chitosan and crosslinker concentration, crosslinker type, and stirring speed as variables. Initial activity of GWE, IMGS and IMGC as antioxidant were confirmed with DPPH method, obtaining a strong activity of 88.01, 82.11, and 84.99% DPPH inhibition at 100 ppm respectively. Promisingly, at concentration of 100 ppm GWE demonstrated AChE inhibition of 30.36%. However, this activity reduced after encapsulation into IMGS and IMGC, with 14.63% and 18.65% AChE inhibition, which can be linked to the relatively sustained diffusion of GWE from the polymer matrix. IMGS and IMGC diffusion profile showed release of 23.24% and 21.89% after 6 hours, with significant increase in diffusion after 24 hours with 74.92% and 71.19% respectively. Despite showing sustained release behaviour, both IMGS and IMGC ex-vivo diffusion significantly improved when compared to GWE which only diffused 51.84% after 24 hours. This result indicates encapsulation of GWE into a polymeric carrier could increase gambier diffusion through the nasal mucous membrane, significantly improving the potential to penetrate into the brain systemic circulation. Combined with desirable intranasal delivery characteristics, this research was able to demonstrate the promising potential of gambier water extract polymeric system as AChE inhibitors for AD therapy.